The Role of Islamic Micro Financial Cooperatives (Baitul Maal Wat Tamwil) in Local Economic Development - Sofana, R D Putra (Universitas Negeri Semarang, 2022)
Indonesia, the largest Moslem country in the world, is still facing chronic poverty problems. Despite the fact that GDP per capita has shown a positive trend since the financial crisis that hit Indonesia in mid 1997, it is not difficult to see that poverty and inequality still prevail in reality. There is widening gao between those who control main business and the poor.. According to the Indonesia Central Bureau of Statistics, around 17.75 percent of total population (around 220 millions) are still living under poverty line. The poor themselves have underutilized entrepreneurship potential due to the structural barriers in economic activities. Microfinance is an alternative for micro entrepreneurs and the poor, who are normally not eligible or bankable to receive loans from commercial banks.